Axiology of the Province Phenomenon in Russian Mass Media of the Beginning of the 21st Century - O. D. Parshina (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The article presents the results of a study of value meanings of the province phenomenon in the discursive environment of the Russian mass media at the beginning of the 21st century. The basic semantics of the Russian lexeme provintsiya is described based on the data of the explanatory dictionaries of the Russian language. The analysis is made of adjectival and verbal combinations selected by a continuous sampling method from the materials of the National Corpus of the Russian Language. The categories based on which the value semantics of the province in time and space are identified are defined. In accordance with the established categories, the selected adjectival and predicative combinations were distributed, and their estimation scaling was performed in relation to positive and negative evaluation. It is established that at the beginning of the 21st century the texts of mass media record changes in the value layer of ideas about the province in the language consciousness of modern Russian speakers. Based on the analysis of the dynamics of the axiological component of the lexeme provintsiya, a decrease in negative ratings was recorded with a simultaneous increase in positive ratings since 2006 for adjectival combinations and since 2004 for predicative ones. Dynamic changes in the evaluative meanings accompanying the word provintsiya in the media discourse can be considered as a reflection of the changing role and status of the province in the socio-cultural space of Russia.